Microstructure and electrical characteristics of ITO/CuPc/TCNQ/Al and ITO/TCNQ/CuPc/Al heterojunctions - Theerasak Juagwon (2018)
Microstructure of heterojunction usually has strong influence on its electrical characteristic. In order to study the effect of microstructure, the layers of copper phthalocyanine (CuPc) and tetracyanoquinodimethane (TCNQ) are deposited on indium tin oxide (ITO) coated glass substrate by thermal evaporation method. The modification of microstructure in the organic semiconductor layer with varied underneath layer is studied in the heterojunction between CuPc and TCNQ. Then the effect on its electrical characteristic is examined between ITO and aluminum (Al) electrodes in these alternative structures. By determining the microstructure by atomic force microscope (AFM), the CuPc and TCNQ thin films provide very tiny and large grain, respectively. These large grains in TCNQ thin film connect into line pattern probably due to the slow grain growth. Therefore the CuPc film is deposited on this TCNQ layer, the larger gain size of CuPc film can be achieved. However, the TCNQ layer grown on top of tiny grain of CuPc exhibits relatively small grain size. The variation of X-ray diffraction (XRD) peaks of these alternative structures support the microstructure extracted from AFM image very well. The optical absorption of these various structures exhibits the combination of absorption peaks from each layer. The electrical characteristics of these structures strongly depend on junction between ITO electrode and organic layer. The heterojunction structures of ITO/CuPc/Al and ITO/CuPc/TCNQ/Al show rectifier characteristics while the structures of ITO/TCNQ/Al and ITO/TCNQ/CuPc/Al exhibit similar IV characteristic for both polarities. However the effect of larger grain size in TCNQ layer leads to very much higher current than those other structures. By measuring current down to temperature of 50 K, it is found that the structures with rectifier junction indicate the current decreasing more than five orders of magnitude while the junctions with no rectifier characteristic exhibit only slightly current change even the measured temperature is reduced to very low temperature. © (2012) Trans Tech Publications, Switzerland.